Nanomodified cement composition - D. A. Lyashenko; V. A. Perfilov (Vestnik MGSU)
Introduction. The focus area of construction materials science is to create materials with better performance characteristics. The most common construction material is concrete that has various purposes. The development of the construction industry leads to the design of increasingly complex structures, whose construction requires high-performance concretes featuring greater reliability.Materials and methods. Reported research data on using various nano-modifying additives for concrete are presented. Co-using carbon nanotubes (CNT) and plasticizer SP-3, as well as adding the nano-modifying additive by the method of ultrasonic dispersion are proposed as a composite additive for concrete.Results. The results of a series of tests are presented. The tests were aimed at studying the effect of a composite additive on the strength characteristics of fine-grained concrete. An increase in the compressive strength of concrete modified with CNTs was detected. Electron microscopy was employed to find that the use of nanomaterials changes the structure of concrete at micro- and nano-scale levels.Conclusions. Electron microscopy studies show the presence of fine-grained concrete areas modified with carbon nanotubes. However, this nano-modifying additive does not spread throughout the entire mixture. Therefore, additional actions should be considered to make the components spread throughout the mixture. The use of different type of mixers can have a positive effect on the dispersion of CNTs.